The application of matrix rhythm therapy as a new clinical modality in burn physiotherapy programmes - ÖZGÜL, BAHAR; POLAT, MİNE GÜLDEN; AYDOĞDU, ONUR; YURDALAN, SAADET UFUK; SARI, ZÜBEYİR (ELSEVIER SCI LTD, 2014)
Purpose: The aim of the present study was to investigate the use of matrix rhythm therapy (MRT) as one of the electrotherapeutic modalities in clinics. Methods: This study was carried out in the Burn and Wound Treatment Department of Dr. Lutfi Kirdar Kartal Education and Research Hospital in Istanbul between October 2010 and August 2011. A treatment protocol including whirlpool, MRT and exercise was applied to a group of patients who had burn injury of upper extremity. The evaluation of each patient included assessment of pain, range of motion, muscle strength, skin flexibility and sensory function at pre- and post-treatment. Results: There was no significant difference in values of pain, muscle strength and flexibility between pre- and post-treatment assessments (p > 0.05). A significant increase was found in the range of motion and sensory function at pre-treatment according to post-treatment (p < 0.01). Conclusion: The usage of MRT in order to maintain and improve the range of motion and to minimise the development of scar tissue was investigated in this study. We suggest conducting randomised controlled studies that carry out a comparison of the MRT with other treatment modalities with more cases and investigate the long-term effects of MRT. (C) 2013 Elsevier Ltd and ISBI. All rights reserved.
Keywords: Matrix Rhythm Therapy; Burns; Physiotherapy and rehabilitation; REHABILITATION; STRENGTH